2009
DOI: 10.3892/or_00000565
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular alterations associated with oral squamous cell cancer (Review)

Abstract: Abstract. The development of oral squamous cell cancer (OSCC) is a multistep process involving the accumulation of multiple genetic alterations modulated by genetic predisposition and environmental influences such as tobacco and alcohol use, chronic inflammation, and viral infections. All of these factors can lead to a wide range of genetic and molecular alterations that can be detected using a range of molecular studies. The alterations mostly affect two large groups of genes: oncogenes and tumor suppressor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 33 publications
(36 reference statements)
0
71
0
2
Order By: Relevance
“…An oral squamous cell carcinoma (OSCC) is a tumor characterized by multiple multistep genetic alterations, that lead to genomic instability and disordered cell growth due to oncogene overexpression, subexpression of tumor-suppressor genes and other genetic, epigenetic and microRNA alterations (1)(2)(3)(4)(5). The two most studied oncogenes (dominant) in human solid tumors are HER-2/neu and c-myc; while p53 is a tumor-suppressor gene involved in almost all human malignancies (6).…”
Section: Introductionmentioning
confidence: 99%
“…An oral squamous cell carcinoma (OSCC) is a tumor characterized by multiple multistep genetic alterations, that lead to genomic instability and disordered cell growth due to oncogene overexpression, subexpression of tumor-suppressor genes and other genetic, epigenetic and microRNA alterations (1)(2)(3)(4)(5). The two most studied oncogenes (dominant) in human solid tumors are HER-2/neu and c-myc; while p53 is a tumor-suppressor gene involved in almost all human malignancies (6).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of OSCC remains dismal as more than 50% of the patients die of this disease or complications within 5 years under current therapies (2). To increase patient survival rate, investigations elucidating the mechanisms of tumorigenesis in OSCC are urgently needed (2).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of OSCC remains dismal as more than 50% of the patients die of this disease or complications within 5 years under current therapies (2). To increase patient survival rate, investigations elucidating the mechanisms of tumorigenesis in OSCC are urgently needed (2). Some studies have suggested that subsets of cancer stem cells (CSC) or tumor initiating cells (TICs) are responsible for tumor progression as well as recurrence after conventional chemotherapy (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenes and tumor suppressor genes are the two major groups of pro-tumorigenic genes which promote tumorigenesis whenever up-regulated or down-regulated, respectively (Hanahan and Weinberg 2000). The down-regulation of tumor suppressor genes is preceded through various epigenetic modifications, mutations, loss of heterozygosities and deletions (Perez-Sayans et al 2009). The epigenetic suppression of genes take place through methylation of CpG islands or histone modifications such as methylation of histone 3, lysine 27 (H3K27) (Rad et al 2016).…”
Section: Introductionmentioning
confidence: 99%